Dried Blood Specimens as an Alternative Specimen for Immune Response Monitoring During HIV Infection: A Proof of Concept and Simple Method in a Pediatric Cohort - Rubio-Garrido, Marina; Avendaño-Ortiz, José; Ndarabu, Adolphe; Rubio, Carolina; Reina, Gabriel; López-Collazo, Eduardo; Holguín, África (Frontiers in Medicine, 2021)
Programs to prevent mother-to-child HIV transmission do not reduce the number of infants exposed during pregnancy and breastfeeding. HIV-exposed but uninfected children (HEU) present higher risk of morbidity and mortality than HIV-unexposed and uninfected children (UU). In this line, the study of immune biomarkers in HIV could improve prediction of disease progression, allowing to diminish comorbidity risk. Dried blood specimens (DBS) are an alternative to serum for collecting and transporting samples in countries with limited infrastructure and especially interesting for groups such as pediatrics, where obtaining a high sample volume is challenging. This study explores the usefulness of DBS for immune profile monitoring in samples from 30 children under clinical follow-up in Kinshasa: 10 HIV-infected (HIV+), 10 HEU, and 10 UU. We have measured the gene expression levels of 12 immune and inflammatory markers (CD14, IL-6, TNFα, HVEM, B7.1, HIF-1α, Siglec-10, IRAK-M, CD163, B7H5, PD-L1, and Galectin-9) in DBS samples by reverse transcription of total RNA and RT-qPCR. Principal component analysis, Kruskal–Wallis test, and Mann–Whitney test were performed in order to study group differences. HIV+ children presented significantly higher levels of seven biomarkers (CD14, IL-6 HVEM, B7.1, Siglec-10, HIF-1α, and CD163) than the UU group. In HEU, we found seven biomarkers significantly elevated (CD14, IL-6, HVEM, B7.1, Siglec-10, HIF-1α, and IRAK-M) vs. UU. Six biomarkers (CD14, IL-6, HVEM, B7.1, Siglec-10, and HIF-1α) showed a significantly higher expression in both HIV+ and HEU vs. UU, with HVEM and CD14 being significantly overexpressed among HIV+ vs. HEU. Our data reveal the utility of DBS for immune response monitoring. Moreover, significant differences in specific biomarker expression across groups strongly suggest the effect of HIV infection and/or HIV exposure on these immune biomarkers' expressions.